Hsc70 is a novel interactor of NF-kappaB p65 in living hippocampal neurons. - Christin Klenke (Public Library of Science (PLoS), 2013)
Signaling via NF-κB in neurons depends on complex formation with interactors such as dynein/dynactin motor complex and can be triggered by synaptic activation. However, so far a detailed interaction map for the neuronal NF-κB is missing. In this study we used mass spectrometry to identify novel interactors of NF-κB p65 within the brain. Hsc70 was identified as a novel neuronal interactor of NF-κB p65. In HEK293 cells, a direct physical interaction was shown by co-immunoprecipitation and verified via in situ proximity ligation in healthy rat neurons. Pharmacological blockade of Hsc70 by deoxyspergualin (DSG) strongly decreased nuclear translocation of NF-κB p65 and transcriptional activity shown by reporter gene assays in neurons after stimulation with glutamate. In addition, knock down of Hsc70 via siRNA significantly reduced neuronal NF-κB activity. Taken together these data provide evidence for Hsc70 as a novel neuronal interactor of NF-κB p65.